A flagship for Austral temperate forest conservation: an action plan for Darwin's frogs brings key stakeholders together. Issue 3 (17th May 2021) - Azat, Claudio; Valenzuela-Sánchez, Andrés; Delgado, Soledad; Cunningham, Andrew A.; Alvarado-Rybak, Mario; Bourke, Johara; Briones, Raúl; Cabeza, Osvaldo; Castro-Carrasco, Camila; Charrier, Andres; Correa, Claudio; Crump, Martha L.; et al.
Abstract: Darwin's frogs Rhinoderma darwinii and Rhinoderma rufum are the only known species of amphibians in which males brood their offspring in their vocal sacs. We propose these frogs as flagship species for the conservation of the Austral temperate forests of Chile and Argentina. This recommendation forms part of the vision of the Binational Conservation Strategy for Darwin's Frogs, which was launched in 2018. The strategy is a conservation initiative led by the IUCN SSC Amphibian Specialist Group, which in 2017 convened 30 governmental, non-profit and private organizations from Chile, Argentina and elsewhere. Darwin's frogs are iconic examples of the global amphibian conservation crisis: R. rufum is categorized as Critically Endangered (Possibly Extinct) on the IUCN Red List, and R. darwinii as Endangered. Here we articulate the conservation planning process that led to the development of the conservation strategy for these species and present its main findings and recommendations. Using an evidence-based approach, the Binational Conservation Strategy for Darwin's Frogs contains a comprehensive status review of Rhinoderma spp., including critical threat analyses, and proposes 39 prioritized conservation actions. Its goal is that by 2028, key information gaps on Rhinoderma spp. will be filled, the main threats to these species will be reduced, and financial, legal and societal support will have been achieved. The strategy is a multi-disciplinary, transnational endeavour aimed at ensuring the long-term viability of these unique frogs and their particular habitat.